2011
DOI: 10.1029/2011ja016539
|View full text |Cite
|
Sign up to set email alerts
|

Near-Earth plasma sheet azimuthal pressure gradient and associated auroral development soon before substorm onset

Abstract: [1] The azimuthal plasma pressure gradient in the near-Earth plasma sheet makes crucial contributions to field-aligned current (FAC) formation. Numerical simulations and statistical observations have shown that a plasma pressure peak tends to build up in the premidnight region of the near-Earth plasma sheet during the substorm growth phase owing to enhanced magnetic drift. This leads to azimuthal pressure gradients in this region. The temporal variation of the azimuthal pressure gradient may provide an indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 54 publications
5
67
0
Order By: Relevance
“…Xing et al (2011) reported similar results that the azimuthal pressure gradient increases between substorm initial brightening and poleward expansion. It slightly decreased at ∼0337 UT, just before the first pseudosubstorm subsided.…”
Section: Magnetotailsupporting
confidence: 56%
“…Xing et al (2011) reported similar results that the azimuthal pressure gradient increases between substorm initial brightening and poleward expansion. It slightly decreased at ∼0337 UT, just before the first pseudosubstorm subsided.…”
Section: Magnetotailsupporting
confidence: 56%
“…For example, Saito et al [2010] presented global auroral images taken by the Polar satellite during substorm expansion, to show that the auroral evolution is spatially and temporally separable into two periods of intense auroral activities, which were separated by 4.5 min. [Lui, 1996], dawnward inertial currents [Shiokawa et al, 1997], pressure gradients [Shiokawa et al, 1998;Birn et al, 1999;Yao et al, 2012], flow vortices near the equatorial plane [Birn et al, 2004;Keiling et al, 2009], and low-entropy magnetic flux tubes (or plasma bubbles) [Sergeev et al, 1996;Chen and Wolf, 1999;Nakamura et al, 2001;Birn et al, 2004;Xing et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…In this case study good agreement was found between the magnitude of the FAC sheet current pair as obtained by FAST and Polar in a simultaneous coordinated measurement. The azimuthal plasma pressure gradient of 0.01 nPa/R E used in our calculations is characteristic of quiet times [Xing et al, 2011] and it was sufficient to power the auroral current system as seen by the two satellites. As the pressure gradient current generation is proportional to 1/B it is highly dependent on the configuration of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…This was a remarkably successful statistical study considering the averaging over different geophysical conditions and the use of the magnetic field model to map low altitude satellite data to model magnetospheric particle densities and temperatures. With the advent of multi satellite missions such as CLUSTER and THEMIS, it is now possible to make direct measurements of the plasma pressure and hence its gradient [Xing et al, 2011]. These measurements show that during quiescent times the night side azimuthal pressure gradients are of the order of 0.01 nPa/Re and it can increase by a large factor before and during substorm onset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation